Стан загальносоматичного здоровя дітей Прикарпаття = State of Precarpathian children's somatic health - M. A. Luchynskyy (Kazimierz Wielki University, 2015)
Luchynskyy M. A. Стан загальносоматичного здоровя дітей Прикарпаття = State of Precarpathian children's somatic health. Journal of Education, Health and Sport. 2015;5(10):91-97. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32503 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A91-97 https://pbn.nauka.gov.pl/works/659791 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015. УДК 613.95   Стан загальносоматичного здоровя дітей Прикарпаття   State of Precarpathian children's somatic health   Лучинський М. А. M. A. Luchynskyy   ДВНЗ «Тернопільський державний медичний Університет імені І. Я.  Горбачевского МОЗ України»,   SHEI "I Horbachevsky Ternopil State Medical University Healthcare Ministry of Ukraine"   Лучинський М.А. завідуючий кафедрою терапевтичної стоматології ДВНЗ «Тернопільський державний медичний університет імені І.Я.  Горбачевского МОЗ України», д-р мед. наук, доцент, Україна, м. Тернопіль   Резюме                         В даній статті приведений аналіз рівня загальносоматичної патології у дітей, які проживають у різних клімато-географічних регіонах Прикарпаття, з різним антропогенним навантаженням на організм дитини. Доведено, що у дітей антропогенно несприятливих регіонів проживання знижена резистентність організму, що підтверджується збільшенням частоти скарг та частоти загально соматичних захворювань.   Ключові слова: діти, захворюваність, клімато-географічний регіон.   STATE OF PRECARPATHIAN CHILDREN'S SOMATIC HEALTH M. A. Luchynskyy (Ternopil) SHEI "I Horbachevsky Ternopil State Medical University Healthcare Ministry of Ukraine"   Summary   This article analyzes the level of somatic diseases in children living in various climato-geographical regions of the Precarpathians, with varying anthropogenic load on the organism of the child. It has been proved that organism resistance of children from anthropogenic unfavorable regions is reduced, that is approved by increased frequency of complaints and the frequency of somatic diseases.   Tags: children, morbidity, climato-geographical region.